Pengaruh Beban Pajak Tangguhan, dan Perencanaan Pajak Terhadap Manajemen Laba : Studi Empiris Pada Perusahaan Subsektor Asuransi yang terdaftar di Bursa Efek Indonesia Tahun 2021-2024 - Muhammad Idris Nasution; Ferry Irawan (CV. Ulil Albab Corp, 2026)
This study aims to analyze: (1) the effect of deferred tax burden on earnings management, and (2) the effect of tax planning on earnings management in insurance sub-sector companies listed on the Indonesia Stock Exchange for the 2021–2024 period. This study uses a quantitative approach with a purposive sampling method. The research sample consists of 15 insurance sub-sector companies listed on the Indonesia Stock Exchange during the observation period of 2020–2024. The data used are secondary data obtained from the company's financial statements and then analyzed using statistical methods through the Stata application version 17. The results of the study indicate that deferred tax burden and tax planning have a positive and significant effect on earnings management. This finding indicates that an increase in deferred tax burden and tax planning activities tends to be followed by an increase in earnings management practices in insurance sub-sector companies listed on the Indonesia Stock Exchange.